Porous alumina–hydroxyapatite composites through protein foaming–consolidation method - Sopyan, Iis; Fadli, Ahmad; Mel, Maizirwan (Elsevier, 2012)
This report presents physical characterization and cell culture test of porous alumina–hydroxyapatite (HA) composites fabricated through protein foaming–consolidation technique. Alumina and HA powders were mixed with yolk and starch at an adjusted ratio to make slurry. The resulting slip was poured into cylindrical shaped molds and followed by foaming and consolidation via 180 °C drying for 1 h. The obtained green bodies were burned at 600 °C for 1 h, followed by sintering at temperatures of 1200–1550 °C for 2 h. Porous alumina–HA bodies with 26–77 vol.% shrinkage, 46%–52% porosity and 0.1–6.4 MPa compressive strength were obtained. The compressive strength of bodies increased with the increasing sintering temperatures. The addition of commercial HA in the body was found to increase the compressive strength, whereas the case is reverse for sol–gel derived HA. Biocompatibility study of porous alumina–HA was performed in a stirred tank bioreactor using culture of Vero cells. A good compatibility of the cells to the porous microcarriers was observed as the cells attached and grew at the surface of microcarriers at 8–120 cultured hours. The cell growth on porous alumina microcarrier was 0.015 h−1 and increased to 0.019 h−1 for 0.3 w/w HA-to-alumina mass ratio and decreased again to 0.017 h−1 for 1.0 w/w ratio.